IMPLEMENTASI MAKNA TINDAK TUTUR IMPERATIF TIDAK LANGSUNG ANTAR TOKOH DALAM ANIME KUROSHITSUJI「黒執事」KARYA YANA TOBOSO - I Wayan Arip Kertanegara; Anak Agung Ayu Dian Andriyani; Ni Wayan Meidariani (Universitas Negeri Padang, 2021)
This study examines the implementation of the meaning of indirect imperative speech acts contained in the dialogue between the anime characters Kuroshitsuji 「黒執事」. The data sources used in this study are the dialogues contained in the Kuroshitsuji「黒執事」 anime. This study uses a qualitative descriptive method, the methods and data collection techniques used are listening and note-taking techniques. The method and technique of presenting the results of data analysis used is an informal method. The results of this study found that indirect imperative speech acts are manifested in two forms, namely indirect imperative speech acts in news sentences (declarative) and interrogative sentences (inrogative). Based on the category of meaning, the meaning of indirect imperative speech acts embodied in news sentences (declarative) and interrogative sentences (interrogative) is divided into 4, namely: the imperative meaning of Meirei's order (命令), the meaning of the imperative of Kinshi's prohibition (禁止), the imperative meaning of Irai's request (依頼) and the imperative meaning of Kanyuu's invitation (勧誘).